Management informacij v izobraževanju - Tratnik, Monika (Teorija in praksa, 2000)
The paper draws on a research that was conducted during author's doctoral studies at the Institute of Education, University of London. Having the right information, at the right time is becoming one of the central issues in all areas of education. Nowadays information is structured and managed by the so called information systems, being larger and more complex than computer tools.The paper therefore first presents certain sociological aspects of information systems in education. The preposition here is, that in post-industrial societies, aims of educational information systems, then the ways of how information is collected and communicated and therefore managed, are changing in specific ways. Two ideal typical models, fordist and postfordist educational management information system (EMIS), were developed as a methodological tool and were empirically explored in England and Slovenia.
Keywords: management; izobraževalni sistemi; informacije; education; izobraževanje; primerjalna analiza; informacijski sistemi; England; Anglija; Slovenia; Slovenija